2023
DOI: 10.1186/s12888-023-05195-9
|View full text |Cite
|
Sign up to set email alerts
|

Prescription drugs with potential for misuse in Irish prisons: analysis of national prison prescribing trends, by gender and history of opioid use disorder, 2012 to 2020

Louise Durand,
Eamon Keenan,
Deirdre O’Reilly
et al.

Abstract: Background Pharmacotherapy is essential for the delivery of an equivalent standard of care in prison. Prescribing can be challenging due to the complex health needs of prisoners and the risk of misuse of prescription drugs. This study examines prescribing trends for drugs with potential for misuse (opioids, benzodiazepines, Z-drugs, and gabapentinoids) in Irish prisons and whether trends vary by gender and history of opioid use disorder (OUD). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In this case, opioid prescribing rates were cut in half between 2015 and 2020, and benzodiazepine and Z-drugs prescribing rates followed a downward trend. In contrast, gabapentinoid prescribing rates increased over the study period (although they appear to be decreasing in 2020), which was largely driven by pregabalin ( 23 ). It has been reported that there has been an overall decrease in gabapentinoid prescribing in prisons in New South Wales in recent years ( 24 ), suggesting that this issue is also present in Australia.…”
Section: Discussionmentioning
confidence: 89%
“…In this case, opioid prescribing rates were cut in half between 2015 and 2020, and benzodiazepine and Z-drugs prescribing rates followed a downward trend. In contrast, gabapentinoid prescribing rates increased over the study period (although they appear to be decreasing in 2020), which was largely driven by pregabalin ( 23 ). It has been reported that there has been an overall decrease in gabapentinoid prescribing in prisons in New South Wales in recent years ( 24 ), suggesting that this issue is also present in Australia.…”
Section: Discussionmentioning
confidence: 89%